Efficacy of 'Gamadent' toothpaste on the healing of gingival tissues: a preliminary report - Taiyeb-Ali, T.B.; Zainuddin, S.L.; Swaminathan, D.; Yaacob, H. (Nihon University School of Dentistry, 2003)
The aim of this randomised, parallel, double-blind study, in which 28 adult patients diagnosed with chronic gingivitis or early stages of chronic periodontitis were recruited, was to evaluate the efficacy of 'Gamadent' toothpaste compared to a placebo toothpaste. 'Gamadent' toothpaste has all the basic constituents of a toothpaste with the addition of a sea cucumber extract (SCE) of the species Stichopus sp. 1 to improve the healing potential of tissues. The placebo has the same basic constituents minus the extract. Out of the 28 patients, 14 were placed in the test group who used the 'Gamadent' toothpaste, and 14 patients were placed in the control group (2 control subjects defaulted and were excluded), who brushed using the placebo toothpaste. The longitudinal study was carried out over a period of 3 months with assessments made at baseline, 1 month, 2 months and 3 months after conventional therapy at the baseline visit. The clinical parameters used during the trial were Plaque Index (PI), Gingival Index (GI), Papilla Bleeding Index (PBI) and Probing Pocket Depth (PPD). A predetermined number of sites on a molar, premolar, canine and an incisor were examined and evaluated in each quadrant. After the baseline assessment, the patients had full mouth scaling and debridement as well as oral hygiene instructions. Patients were instructed to brush their teeth twice a day with the toothbrush provided (Oral-B plus, size 35) and toothpaste (test or control), using the Bass technique. At the 1-month assessment, there were significant mean reductions to baseline mean values in PI (P < 0.005) and GI (P < 0.001) in the test group as compared to the control group. At the end of the 2-month interval, significant reductions were observed in PI, PBI and PPD (P < 0.001). By the end of 3 months, there were significant differences in the mean reduction of all the parameters i.e. PI, PBI, GI and PPD (P < 0.001), between the test and control sites. In conclusion, 'Gamadent' toothpaste provided noteworthy benefits, producing statistically significant improvement in all clinical parameters compared to the placebo during the healing phase after conventional initial therapy.